The Ask and the Answer - Ness, Patrick, 1971- (Somerville, Mass. : Candlewick Press, 2009)
Alternate chapters follow teenagers Todd and Viola, who become separated as the Mayor's oppressive new regime takes power in New Prentisstown, a space colony where residents can hear each other's thoughts.
A Junior Library Guild selection
Accelerated Reader/Renaissance Learning
Keywords: Space colonies -- Juvenile fiction; Social problems -- Juvenile fiction; Telepathy -- Juvenile fiction; Space colonies -- Fiction; Social problems -- Fiction; Telepathy -- Fiction; Science fiction; Teenagers -- Fiction; Teenage boy/girl relations -- Fiction; Terrorists -- Fiction; Science fiction